The Differences Between Giving Topical Therapy of Extract Etanol 96% and 70% Spirulina Platensis on Density of Collagen Fiber in Traumatic Ulcer Healing - Rizqi Ananda Putri; Nafi’ah; Sarianoferni (Denta Journal Kedokteran Gigi, 2019)
Background: Pravalence of Traumatic Ulcers is quite high in Indonesia. Therapy that has been carried out is still symptomatic, now there are many herbal ingredients that can be used as an alternative ingredients for medicine, including spirulina platensis. Spirulina platensis is one type of biological wealth that is widespread in Indonesian marine waters, and has bioactive ingredients that are beneficial to the body and can help the wound healing process. Purpose: to determine the differences in the effectiveness of topical administration of spirulina platensis ethanol extract 96% and 70% against the density of collagen fibers in healing traumatic ulcers. Materials and Methods: The subjects of the study were 36 wistar rattus novergicus rats divided into 6 groups, treated with traumatic ulcers in the lower labial mucosa, treated according to their respective groups K1.3 (control group 3 days), P1.3 (Giving spirulina gel platensis ethanol extract 96% 3 days), P2.3 (Giving spirulina platensis ethanol extract 70% 3 days), K1.7 (Control group 7 days), P1.7 (Giving spirulina platensis ethanol extract 96% ethanol 7 days ), P2.7 Giving spirulina platensis ethanol extract 70% 7 days 7). Results: There were differences in the effectiveness of giving spirulina platensis ethanol extract 96% and 70%. There is a significant difference in the P1.7 group (score = 4) with P2.7 (score = 3), P1.3 (score = 3) with P1.7 (4), P1.3 (score = 3) with P2 .3 (score 3), K1.3 (score = 2) with P1.3 (score = 3) and P2.3 (score = 3), K1.7 (score = 3) with P1.7 (score = 4) ) and P2.7 (3). Conclusion: There was no difference in effectiveness between 96% and 70% spirulina platensis ethanol extract gel on day 3 and there was a difference in effectiveness between 96% spirulina platensis ethanol extract gel on day 7.